The Role Of The Government And Regional Security Safeguard Team Supervision (TP4D) In Prevention Criminal Corruption - Sarwanto Sarwanto; Sri Endah Wahyuningsih (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The Attorney General of Indonesia issued regulation No Per014 / A / JA / 11/2016. About the guards and security of the government and regional development.This research aims to know and analyze the role of the Government and Regional Development Guards and Security Team in the prevention of corruption, how effective the TP4D is in carrying out its duties and authorities, and what obstacles are found in the field in relation to the duties and authority of the Government and Regional Development Guard and Security Team and how is the solution in providing legal assistance to government administrators to prevent the occurrence of criminal acts of corruption.The research method used is juridical sociology by using primary and secondary data. Primary data collection techniques carried out by interviews, and secondary data by reading, studying and analyzing primary legal materials, secondary legal materials, tertiary legal materials with qualitative analysis techniques, interpreted logically and systematically and drawn conclusions.The conclusion in this study is that the role of the government security guard and regional development (TP4D) team in preventing corruption is passive based on requests from government agencies. The legal product from TP4D is a legal opinion both incidentally and ongoing legal assistance according to the request of government agencies.Keywords: Prosecutors' Office; TP4D; Corruption.